Effect of the interaction between elevated CO2, temperature and drought during regrowth of nodulated alfalfa plants - Erice G.; Irigoyen J.; Sánchez-Díaz M.; Avice J.C.; Ourry A. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The rising atmospheric CO2 concentration resulting from industrial development may change photosynthesis and plant growth. However, there is a lack of information concerning the combined effect of factors such as CO2, temperature and water availability on plant regrowth following cutting or grazing, the usual managing methods of forage legumes like alfalfa. In all Mediterranean regions of the world, summer drought has been recognized as the major stress that limits plant species distribution and growth. The aim of the work was to study the interactive effect of CO2, temperature and water availability in nodulated alfalfa during regrowth. The higher drought tolerance observed during the regrowth period may be related to higher mass and reserves accumulated in the roots. Nitrogen pools in alfalfa taproot, especially vegetative storage proteins (VSP), affect the regrowth of new shoots. After one month of regrowth, drought increased the root VSP concentration.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)